Analisis Minat Belajar Mata Pelajaran IPAS Kelas V SDN Gili Barat - Revolusi, Befa Damai; Mardiyana, Isna Ida; Pritasari, Ade Cyntia (Yayasan Arrahman Nahdlatul Wathan, 2024)
This research aims to determine students' interest in learning in science and science subjects at SDN Gili Barat. This study was conducted at Gili Barat State Elementary School which is located on Jalan Tanjungan, in the Kamal District area, Bangkalan Regency, East Java Province. The research method used is descriptive qualitative. The subjects studied were students in the VA class at SDN Gili Barat with a total of 17 male students and 8 female students. The techniques used are observation, questionnaires and documentation. These VA class students fall into the high class category. The results of the questionnaire stated that Gili Barat Elementary School students liked science and science lessons. The average percentage for each aspect related to preferred activities is 72%, based on conceptual understanding 69%, and based on psychomotor activities 68.8%. Overall, the average response to all aspects measured in the questionnaire shows that students' interest in learning related to science subjects is 69.9%.